Haikyu!!. 10, Moonrise - Furudate, Haruichi, 1983- (Shonen Jump manga., 2017)
After Hinata claims he won't close his eyes for the "Freak Quick" anymore, Kageyama calls him out, and the two fight during the practice game, setting the whole team back. Then, Team Karasuno sees how much better the Tokyo teams are than them, so they will have to either step up, or crumble under the pressure.